2012
DOI: 10.1177/0956797612443370
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Choice Tests Exonerated, at Least of Some Charges

Abstract: Among the criticisms of multiple-choice tests is that-by exposing the correct answer as one of the alternatives-such tests engage recognition processes rather than the productive retrieval processes known to enhance later recall. We tested whether multiple-choice tests could trigger productive retrieval processes-provided the alternatives were made plausible enough to enable test takers to retrieve both why the correct alternatives were correct and why the incorrect alternatives were incorrect. In two experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(83 citation statements)
references
References 30 publications
3
76
4
Order By: Relevance
“…With increasing class sizes or the desire to present multiple exam opportunities, multiple-choice questions are often used to speed up grading. Little, E. Bjork, R. Bjork and Angello (2012) note that multiple-choice tests can be useful learning tools that foster productive retrieval learning. Mathematical analysis of multiple choice tests shows that the fairest method for grading is to give credit for the number of correct answers with no penalty for a wrong or missing answer (Scharf & Baldwin, 2007); this approach, however, does not reduce credit given for blindly guessing an answer (Bush, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…With increasing class sizes or the desire to present multiple exam opportunities, multiple-choice questions are often used to speed up grading. Little, E. Bjork, R. Bjork and Angello (2012) note that multiple-choice tests can be useful learning tools that foster productive retrieval learning. Mathematical analysis of multiple choice tests shows that the fairest method for grading is to give credit for the number of correct answers with no penalty for a wrong or missing answer (Scharf & Baldwin, 2007); this approach, however, does not reduce credit given for blindly guessing an answer (Bush, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Third, accessing information in long-term memory has recently been shown to have beneficial effects on memory under some circumstances. For example, recent work by Little and colleagues examining multiple choice tests (Little & Bjork, 2015;Little, Bjork, Bjork, & Angello, 2012) has suggested that forced-choice memory paradigms need not lead to forgetting of competitors. Given that retrieval can benefit memory under some circumstances, it is not intuitively obvious that forgetting of related visual objects would have occurred in the Maxcey and Woodman paradigm.…”
Section: Are Practiced)mentioning
confidence: 99%
“…Previous studies have also suggested that the inclusion of open-book learning in tests aids retention and understanding (Heijne-Penninga, Kuks, Hofman, Muijtjens, & CohenSchotanus, 2012). In addition, it has been shown that an initial MCQs test not only improves performance for items that are repeated on a final test, but also enhances retrieval of information associated with incorrect alternatives on the initial practice test (Little, Bjork, Bjork, & Angello, 2012).…”
Section: Discussionmentioning
confidence: 99%